2022
DOI: 10.1007/s00382-021-06116-w
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in the relationship between equatorial-mean heat content and interannual eastern equatorial Atlantic sea surface temperature variability

Abstract: Interannual sea surface temperature (SST) variations in the tropical Atlantic Ocean lead to anomalous atmospheric circulation and precipitation patterns with important ecological and socioeconomic consequences for the semiarid regions of sub-Saharan Africa and northeast Brazil. This interannual SST variability is characterized by three modes: an Atlantic meridional mode featuring an anomalous cross-equatorial SST gradient that peaks in boreal spring; an Atlantic zonal mode (Atlantic Niño mode) with SST anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Erfanian et al (2017) found that warmerthan-usual SSTs in the Tropical Pacific (also El Niño events) and Atlantic were the main driving factors behind extreme droughts in South America. However, SST anomalies also results from atmospheric circulation anomalies (Andreas & Hazeleger, 2005;Zhe et al, 2016;Turner et al, 2022). Madden Julian Oscillation (MJO; Zhang 2005) often affects the evolution of SST anomalies; SST anomalies in the tropics can also feedback extratropical circulation anomalies (Lau, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Erfanian et al (2017) found that warmerthan-usual SSTs in the Tropical Pacific (also El Niño events) and Atlantic were the main driving factors behind extreme droughts in South America. However, SST anomalies also results from atmospheric circulation anomalies (Andreas & Hazeleger, 2005;Zhe et al, 2016;Turner et al, 2022). Madden Julian Oscillation (MJO; Zhang 2005) often affects the evolution of SST anomalies; SST anomalies in the tropics can also feedback extratropical circulation anomalies (Lau, 1997).…”
Section: Introductionmentioning
confidence: 99%